Critical care in the emergency department: shock and circulatory support. Issue 1 (20th December 2004) - Graham, C A; Parke, T R J
Abstract : Effective resuscitation includes the rapid identification and correction of an inadequate circulation. Shock is said to be present when systemic hypoperfusion results in severe dysfunction of the vital organs. The finding of normal haemodynamic parameters, for example blood pressure, does not exclude shock in itself. This paper reviews the pathophysiology, resuscitation, and continuing management of the patient presenting with shock to the emergency department.